Global economic institutions - Molle, Willem (London ; New York : Routledge, 2003)
This book explains how global public goods should be defined, how global economic institutions work, and looks at the effect major organizations such as WTO, IMF, etc. have on finance, the environment and transport.
Includes bibliographical references (p. [296]-310) and index.
rpm 24/08/16
Loans
Keywords: International trade agencies; Financial institutions, International; International agencies; International economic organization; Globalization; Globalization